2015
DOI: 10.1109/tr.2014.2385069
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Filtering-Based Discharge Time Prognosis for Lithium-Ion Batteries With a Statistical Characterization of Use Profiles

Abstract: Artículo de publicación ISIWe present the implementation of a particle-filteringbased prognostic framework that utilizes statistical characterization of use profiles to (i) estimate the state-of-charge (SOC), and (ii) predict the discharge time of energy storage devices (lithium-ion batteries). The proposed approach uses a novel empirical statespace model, inspired by battery phenomenology, and particle-filtering algorithms to estimate SOC and other unknown model parameters in real-time. The adaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 38 publications
1
59
0
4
Order By: Relevance
“…Walker et al's [51] research has found that PF is more accurate than the method (nonlinear least squares and an unscented Kalman filter (UKF)) for predicting RUL. Daniel et al [52] presented the implementation of a PF prognostic framework that uses statistical characterization to estimate the state of charge of a battery. The results show that the proposed framework can prognosticate the discharge time in terms of conditional expectations.…”
Section: Rul Prognostics Methodologies Based On Filtering Techniquesmentioning
confidence: 99%
“…Walker et al's [51] research has found that PF is more accurate than the method (nonlinear least squares and an unscented Kalman filter (UKF)) for predicting RUL. Daniel et al [52] presented the implementation of a PF prognostic framework that uses statistical characterization to estimate the state of charge of a battery. The results show that the proposed framework can prognosticate the discharge time in terms of conditional expectations.…”
Section: Rul Prognostics Methodologies Based On Filtering Techniquesmentioning
confidence: 99%
“…To ensure operation within these limits, the SoC value is estimated based on an unscented Kalman filter [35], with outer feedback correction loops as presented in [36]. This is because Bayesian estimation algorithms have been demonstrated to be a well-suited estimation tool for nonlinear problems such as SoC estimation, and they have several advantages including real-time implementation and use of empirical models that better deal with limited and noisy data compared to methods such as ampere-hour counting, internal impedance measurement, and open circuit voltage measurement [37,38].…”
Section: Community Power Controller At the Microgrid Levelmentioning
confidence: 99%
“…. , i n } = {1, 2,8,25,26,32,38,42,43,44,46, 48} and the optimal structure of the model has four rules. Note that exogenous variables were not included in the model.…”
Section: Fuzzy Prediction Interval For Net Power Of the Microgridmentioning
confidence: 99%
“…The defect of this method is that the uncertainty of future load profiles is not considered. In order to predict RDT under uncertain future loads, Pola et al employed a two‐state Markov chain to quantify current transition probability and obtain the interval of future current prediction. It is noted that the existing studies including all mentioned above often overlook some dynamic uncertainties in the prediction process, such as the state estimation uncertainty and future load uncertainty.…”
Section: Introductionmentioning
confidence: 99%